1986
DOI: 10.1007/bf00379255
|View full text |Cite
|
Sign up to set email alerts
|

Physiological consequences of changes in life form of the Mexican epiphyte Tillandsia deppeana (Bromeliaceae)

Abstract: The heterophyllous epiphyte Tillandsia deppeana exhibits an atmospheric habit as a juvenile and a tank form as an adult. Both juveniles and adults utilize C photosynthesis. This is the first report of an atmospheric form of Tillandsia which does not exhibit CAM. Photosynthetic saturation occurred at approximately 10% of full sunlight in both forms, but the adults exhibited greater rates of photosynthesis at all levels of irradiance. The adults also had a higher and broader photosynthetic temperature optimum th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
2

Year Published

1986
1986
2016
2016

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 29 publications
4
34
0
2
Order By: Relevance
“…Atmospherics tolerate desiccation better than tank species but have lower rates of photosynthesis per unit leaf mass (Benzing and Burt, 1970;Benzing and Renfrow, 1974;Reyes-Garcia et al, 2008), and almost all have CAM photosynthesis (Crayn et al, 2004). Many tank bromeliads exhibit developmental heterophylly, with juveniles starting as atmospherics (Adams and Martin, 1986;Benzing, 2000;Zotz et al, 2011) and then later forming tanks as body size increases. Krömer et al (2006) found that large, tank-epiphyte bromeliads dominated the rainy, moist eastern slope of the Andes in Bolivia, while atmospheric Tillandsia taxa dominated the drier, more seasonal leeward slope.…”
Section: Epiphytism and Fertile Moist Montane Habitats Favor The Tanmentioning
confidence: 99%
“…Atmospherics tolerate desiccation better than tank species but have lower rates of photosynthesis per unit leaf mass (Benzing and Burt, 1970;Benzing and Renfrow, 1974;Reyes-Garcia et al, 2008), and almost all have CAM photosynthesis (Crayn et al, 2004). Many tank bromeliads exhibit developmental heterophylly, with juveniles starting as atmospherics (Adams and Martin, 1986;Benzing, 2000;Zotz et al, 2011) and then later forming tanks as body size increases. Krömer et al (2006) found that large, tank-epiphyte bromeliads dominated the rainy, moist eastern slope of the Andes in Bolivia, while atmospheric Tillandsia taxa dominated the drier, more seasonal leeward slope.…”
Section: Epiphytism and Fertile Moist Montane Habitats Favor The Tanmentioning
confidence: 99%
“…Almost all studies related to bromeliad size have focused on the measurement of the responses of the photosynthetic apparatus, gas exchange, transpiration rates and morphological changes in relation to environmental factors (Adams and Martin, 1986a, b;Zotz, 1997;Zotz and Thomas, 1999). For example, adult tank-forming bromeliads under well-watered conditions show higher rates of CO 2 exchange and transpiration than smaller ones (Adams and Martin, 1986a). Many bromeliads with a rosette growth pattern have the ability to form a tank and store water to avoid drought.…”
Section: Raiza J Castillo Et Almentioning
confidence: 99%
“…In these taxa, early juveniles are atmospheric, while later stages have broad leaves which form a water-impounding tank. Apart from many morphological differences (Adams & Martin 1986a), larger individuals of Tillandsia deppeana show significantly higher rates of CO 2 exchange and transpiration, and differ strongly in stomatal behaviour after the onset of drought (Adams & Martin 1986b). Conceptually, however, these studies did not represent much progress, because in both cases the authors treated the differences between "juvenile" and "adult" as step-like changes in plant form.…”
Section: Plant Size -Demographic and Physiological Aspectsmentioning
confidence: 99%